Adolphe Adam, master of the opéra-comique, 1824-1856 - Letellier, Robert Ignatius 1953-; Fuller, Nicholas Lester (Cambridge Scholars Publishing, 2024)
The composer Adolphe-Charles Adam (1803-1856) is known all over the world for the famous Christmas anthem ‘Minuit chrétiens’ (‘O Holy Night’). However, he wrote much more than just this. His ballet Giselle (1841) is the quintessence of mystical Romanticism and one of the most enduring works of the dance repertoire. Adam composed a series of ballets, principally for the Paris Opéra, establishing this genre as a serious and integral musical form. His last work was Le Corsaire (1856) which reaches sublime heights. However, Adam was just as famous as a composer for the lyric stage. With Boieldieu, Hérold and Auber, he forms one of the quartet of masters that represent the second school of that profoundly French genre of the opera-comique. The charming and elegant Le Chalet (1834) received over 1500 performances in Paris, and the exuberant and adorable Le Postillon de Lonjumeau (1836) is still played on stages throughout the world. This study considers this gentle, unassuming composer’s life and work, examining his 42 operas and 14 ballets in the context of the vibrant musical scene in Paris during the decades 1820-1860.